\(B=2x^2-5x+3\)
\(=2\left(x^2-\frac{5}{2}x+\frac{3}{2}\right)\)
\(=2\left(x^2-\frac{5}{2}x+\frac{25}{16}-\frac{1}{16}\right)\)
\(=2\left[\left(x-\frac{5}{4}\right)^2-\frac{1}{16}\right]\)
\(=2\left[\left(x-\frac{5}{4}\right)^2\right]-\frac{1}{32}\ge\frac{-1}{32}\)
\(B=2x^2-5x+3\)
\(=2\left(x^2-\frac{5}{2}x+\frac{3}{2}\right)\)
\(=2\left(x^2-\frac{5}{4}\cdot2x+\left(\frac{5}{4}\right)^2-\left(\frac{5}{4}\right)^2+\frac{3}{2}\right)\)
\(=2\left[\left(x-\frac{5}{4}\right)^2-\frac{25}{16}+\frac{3}{2}\right]\)
\(=2\left[\left(x-\frac{5}{4}\right)^2-\frac{1}{16}\right]\)
\(=2\left(x-\frac{5}{4}\right)^2-\frac{1}{8}\)
có\(2\left(x-\frac{5}{4}\right)^2\ge0\)
\(\Rightarrow\left(x-\frac{5}{4}\right)^2-\frac{1}{8}\ge-\frac{1}{8}\)
\(\Rightarrow GTNNB=-\frac{1}{8}\)
với \(\left(x-\frac{5}{4}\right)^2=0;x=\frac{5}{4}\)
ミ★长 - ƔξŦ★彡
\(-\frac{1}{16}\cdot2=-\frac{1}{32}\)??????
Kiểm tra lại giùm ạ ._.